أسلوب النداء في تفسير حدائق الروح والريحان لمحمد الأمين الهرري (ت 1441هـ) دراسة بلاغية البحث مستل مِن رسالة ماجستير - البرزنجي, دلسوز جعفر; محمود, حسيبة محمد (Sulaimani Journal for Humanities, 2023)
The method of calling is considered one of the methods of creating a request, which is speech that calls for a desired thing that does not happen at the time of the request. Other methods because of the power of influence it possesses and that it touches human feelings and makes them under its influence. The appeal received ample attention from grammarians and rhetoricians, past and present, and was the focus of attention of interpreters who are interested in the rhetorical aspect of the interpretation of the Holy Qur’an. So we made the call the focus of our research, and after we were exposed to its linguistic and idiomatic definition, we touched on presenting the tools of the call of both types, which are the tools of the near and far calls, and then we mentioned the cases in which each of them proceeds from its origin to its opposite, and then we indicated the rhetorical purposes to which it emerges. the call, Selecting styles from the Holy Qur’an and referring to their interpretation in the interpretations that were concerned with language and rhetoric in their interpretation of the noble Qur’anic verses. In particular, we relied on the interpretation of (Hadayek al-Ruh wa al-Rihan), which is one of the contemporary interpretations that concerned the rhetorical aspect of the methods mentioned in the Holy Qur’an, including this method, and it was the main source relied upon in our research.